DOMINASI IDEOLOGI MEDIA DALAM PROSES PRODUKSI BERITA KASUS AHMADIYAH CIKEUSIK TAHUN 2011 DI MAJALAH TEMPO - Nursatyo Nursatyo (Universitas Nasional, 2017)
The violation of Ahmadiyah adherents in Cikeusik on February 6, 2011 widely reported by various media in Indonesia. One of the media that clearly states its position in defense of Ahmadiyah is a Tempo magazine. Tempo's position is oposite with the dominant view, that Ahmadiyah doctrines are not appropriate and deviate from Islamic doctrines. This article reviews the role of intra and extra media affecting the news production process in Tempo magazine. Through interviews with several informants from Tempo magazine, this study shows that media ideology of Tempo which is liberal, secular and pluralist very dominant with the news production process. Factors individuals, organizations, and extra media is subordinate to Tempo ideology. Even the media routines further strengthen Tempo ideology. In its news, Tempo seeks to follow the principle of journalism, that is the voice of the oppressed. Tempo considers Ahmadiyah as a oppressed group because always being the victims of violence from those who represent the dominant view.